NILAI-NILAI DAN MAKNA BIMBINGAN KONSELING ISLAM DALAM HADIS SAHĪH BUKHĀRĪ (STUDI HADIS TENTANG RUKUN ISLAM) - Zulfa, Nadhifatuz (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
Human life is full of problems as trials, trials and even warnings from God. If he does not internalize the value and meaning contained in the pillars of Islam, it will be far from the potential / nature of religious. Efforts to apply the values and meanings conceived of the pillars of Islam in running a life full of this problem is an Islamic counseling guidance strategy that helps people find their fitrah as khalīfah and servant of God on earth. The content of hadith S{ahīh{ Bukhārī about Pillars of Islam is this hadith is a high hadith position. The values of Islamic guidance and counseling contained in this hadith include the aqīdahvalue includes the vision and mission of guidance and counseling of Islam, especially in shahadah and pilgrimage, as well as optimism and inner calm, Shari'ah values include actions lahiriyah or activities (practice / action) in the guidance and counseling of Islam, the value of Social / Muamalah include empathy, social care, compassion, help in the goodness, unity and unity, equality and brotherhood, togetherness (jamāah), and the value of morals include out put counseling and counseling Islam, isakhlâqulkarîmah, with the formation of muttaqîn. While the meaning of guidance and counseling Islam contained in the pillars of Islam is guidance / direction, prevention, aid, directed, systematic, understanding, alleviation, development / improvement, religious nature, and harmonious